The impact of vitamin A supplementation given during a pneumonia episode on the subsequent morbidity of children - Nacul, Luis C.; Arthur, Paul; Kirkwood, Betty R.; Morris, Saul Sutkover; Carneiro, A. C.; Benjamin, A. F. (Wiley, 1998)
objective To evaluate the impact of large‐dose vitamin A supplementation given to infants > 6 months old (200 000 IU) and to preschool children aged 1–4 years (400 000 IU) during a pneumonia episode, on their subsequent morbidity and severe morbidity.method In a randomized, double‐blind, placebo controlled trial, the children were followed‐up with 2‐weekly visits at home for 16 weeks, with the first visit 2 weeks after treatment for pneumonia was initiated. The field workers asked about the presence of morbidity on the day of the visit and in the previous two weeks and about the occurrence and number of clinic attendances and hospital admissions since the last visit. They also measured the patients' respiratory rate and temperature and assessed the children for the presence of cyanosis, chest indrawing and wheezing.results Except for the prevalence of diet refusal which was higher in the vitamin A group, no differences between the study groups were observed, either in the prevalence of morbidity or in the incidence of clinic attendances and hospital admissions.conclusion No evidence was found for a beneficial effect of vitamin A given during acute pneumonia on the subsequent morbidity and severe morbidity of children in a population with marginal vitamin A deficiency.